MOLLUSKS ON RECRUITMENT PANELS PLACED IN AN OFFSHORE HARBOR IN TROPICAL NORTHEASTERN BRAZIL - Barroso, Cristiane Xerez; Rabay, Soraya Guimarães; Matthews Cascon, Helena (Arquivos de Ciências do Mar, 2018)
In order to contribute to knowledge of marine fouling communities, the present study analyzed the temporal variation in molluscan communities found on quarterly and annual recruitment panels placed in a seaport area of northeastern Brazil. A set of 30 artificial panels was submerged among pier pillars to a depth of approximately 6 m. Every three months, one subset of 15 panels was removed to examine the biota present. The second subset of 15 panels was left submerged for one year, and then removed for analysis. On the same day that the panels were removed, they were replaced with new panels. Twelve removals/replacements of panels were performed from October 2009 to November 2012. Two classes of Mollusca were found in the recruitment panels: Gastropoda and Bivalvia. Thirty taxa were found in the quarterly panels, and 23 taxa in the annual panels. Two non-native species of the Brazilian coast were found: Isognomon bicolor and Eualetes tulipa. In the quarterly panels, the most abundant and common species found was the oyster Crassostrea brasiliana and the most abundant species found in the annual panels was Musculus lateralis.